Hubungan Antara Phbs Rumah Tangga Dengan Kejadian Ispa Balita Di Desa Sindon Kabupaten Boyolali - Tiara Putri Navy; Abi Muhlisin (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Currently, ARI has become a cause of death in toddlers worldwide. The etiology of ARI is caused by viruses and bacteria. In addition, it can be in the form of nutrition, exclusive breastfeeding, and environmental conditions (Asrianto et al., 2022). Minimal instillation or not knowing the instructions for Clean and Healthy Living Behavior (PHBS) in households also makes it possible to get ARI (Zolendo et al., 2022). This study aims to determine the relationship between household PHBS and the incidence of ARI in toddlers in Sindon Village, Boyolali Regency. The type of research used in this study is quantitative with a correlation analytical method. The sample selection technique is by using the purposive sampling method, and 74 respondents have been determined. The instruments in the study were the household PHBS attitude questionnaire and the toddler ARI incidence questionnaire. The results of the Chi-Square statistical test obtained a p-value of 0.001 (<0.05), so it can be interpreted that there is a relationship between household PHBS and the incidence of ARI in toddlers in Sindon Village, Boyolali Regency. The good PHBS attitude of parents will determine the possibility of ARI in toddlers. The majority of respondents behaved well and did not experience ARI. Judging from the output of this study, health education is needed regarding PHBS in household settings and ARI in the community. Priority should be given to individuals who have moderate PHBS attitudes and experience ARI.